Influence of the heat treatment procedure on the stress corrosion cracking behaviour of low pressure turbine blade material FV566 - Seumangal, Nicole (Centre for Materials Engineering, 2018)
Stress corrosion cracking is one of the leading damage mechanisms in low-pressure turbines in the power generation industry; in LP turbine blades it primarily occurs in the last stage blades. The research investigated the influence of tempering temperature on the microstructure, mechanical properties, and stress corrosion cracking properties of 12% chromium FV566 stainless steel, which is used to manufacture LP turbine blades. The standard heat treatment of the steel comprises of austenitising, quenching and double tempering. Austenitising is carried out at 1050°C for one hour - which is sufficiently long to generate a fully austenitic matrix and to dissolve carbon completely. Subsequently, the material is quenched in air. The high level of alloying elements ensures the complete martensitic transformation, with carbon atoms trapped in the matrix and distributed homogeneously. Thereafter, tempering of the material at 580-600°C enhances the ductility and toughness. Tempering replaces the solid solution strengthening of the dissolved carbon with precipitation strengthening by carbides. The final microstructure of the FV566 steel blades is referred to as tempered martensite. van Rooyen showed that for 12% chromium steel tempering at and above 600°C induces passivity of the material against SCC, while tempering of 12% chromium steels at 450-550°C causes sensitisation of the material and the material exhibits intergranular SCC. From such studies, the motivation arises to investigate the impact of heat-treatment parameters - specifically the impact of tempering temperature on the stress corrosion behaviour of the material. The testing methodology comprises heat treatment of FV566 samples at 1050°C for 1 hour, at 350°C for 1 hour, and thereafter tempering for 1 hour at various tempering temperatures. Each stage of heat treatment is followed by air cooling - followed by analysis of the microstructure, mechanical testing and stress corrosion cracking testing of the specimens at the different temper conditions. Stress corrosion testing was divided into two categories. The first set of tests was carried out with U-bend specimens to determine the susceptibility of materials at different heat treatments to SCC, the time taken for SCC to initiate, and the mode of cracking. The second set of tests was conducted to determine the threshold stress intensity, as a function of crack growth rate, for each heat treatment. The SCC failure mechanism observed was intergranular SCC (IGSCC) by anodic dissolution for the 550°C, 560°C, 570°C, 580°C, 590°C, 600°C and 620°C specimens. The material's resistance to SCC improved with increasing tempering temperature. Specimens tempered at 480°C and 550°C were most susceptible to SCC, while specimens tempered at 600°C The material's resistance to SCC improved with increasing tempering temperature. Specimens tempered at 480°C and 550°C were most susceptible to SCC, while specimens tempered at 600°C were immune to SCC in a 4000-hour period. A change in tempering temperature results in a change in the quantity and type of precipitates formed which results in changes in SCC properties of FV566.